A Significant Genetic Admixture in Farmed Populations of the Noble Scallop Chlamys nobilis Revealed by Microsatellite DNA Analysis in Southern China - Ma, Haitao; Yu, Dongmei; Xiao, Shu; Qin, Yanping; Zhang, Yang; Li, Jun; Zhang, Yuehuan; Yu, Ziniu (Frontiers in Marine Science, 2021)
The noble scallop, Chlamys nobilis, is an important fishery and aquaculture species in the coastal region of southern China. However, limited information is available about its genetic diversity and stock structure. Using ten microsatellite loci, four cultivated populations of C.nobilis were compared with one another and with a wild population in southern China. A total of 83 alleles were found across all of the loci. A high level of genetic diversity was found within the wild population and cultivated populations, and a higher genetic diversity was detected in the four cultivated populations compared with the wild population. Although the wild population was completely in Hardy-Weinberg equilibrium, significant deviations from the Hardy-Weinberg equilibrium were found in all of the cultivated populations due to heterozygote deficiency, suggesting a genetic admixture caused by seeds being mixed from various hatcheries. Fst and AMOVA values showed significant genetic differences between the wild and cultivated populations. The Bayesian assignment also confirmed that the genetic admixture was significant and widespread in artificial breeding of C.nobilis. Furthermore, UPGMA tree topology and PCA showed a clear division between the wild and cultivated populations. The information about the genetic variation and differentiation in cultivated and wild populations obtained in this study is useful for setting up suitable guidelines for founding and maintaining cultured stocks and for protection of future wild populations.